Semaglutide Associated with Central Serous Chorioretinopathy: A Case Report - Rodrigues, Lívia Peregrino; Rubatino, André Lucas Loureiro; Rubatino Junior, Antônio Carmo; Rodrigues, Juliano Flávio Rubatino; Rubatino, Fernando Victor Martins; Araújo Filho, Gerardo Maria de (Brazilian Journal of Case Reports, 2025)
This clinical case examines central retinal serous chorioretinopathy in a patient undergoing treatment with semaglutide. The subject of the case is a middle-aged male who developed this retinal condition following the administration of 14 mg of oral semaglutide. He reported a variety of vision-related disturbances that significantly impacted his daily activities. Fortunately, the visual impairments were completely resolved upon discontinuation of the medication. This case underscores the critical importance of vigilant ophthalmological monitoring for patients receiving semaglutide. It is imperative to monitor for any potential adverse effects on vision, thereby facilitating the prompt recognition and management of any changes or complications. By prioritizing regular eye examinations, healthcare providers can protect patients' visual health and promptly address any issues that may arise during their treatment.